Vocal Training Mitigates Age-Related Changes Within the Vocal Mechanism in Old Rats - Johnson, Aaron M. (Oxford University Press, 2013)
Aging affects voice production and is associated with reduced communicative ability and quality of life. Voice therapy is a critical component of treatment, but its effects on neuromuscular mechanisms are unknown. The ultrasonic vocalizations (USVs) of rats can be used to test the effects of aging and voice use on the laryngeal neuromuscular system. This study tested the hypothesis that age-related changes in the USVs of rats and laryngeal neuromuscular junctions can be reversed through vocal exercise. Young and old rats were trained for 8 weeks to increase their USVs and were compared with a no intervention group pre- and post-treatment. USV acoustics and aspects of neuromuscular junction (NMJ) morphology were measured in the thyroarytenoid muscle. Vocal training reduced or eliminated some age differences found in both USVs and NMJs. We conclude that vocal exercise may assist in mitigating age-related changes in voice characteristics and underlying neuromuscular adaptations.